When the Fed sneezes: Spillovers from U.S. monetary policy to emerging markets - Annette Meinusch (Philipps-University Marburg, School of Business and Economics, 2017)
This paper aims to shed light on the role mean and volatility spillovers of U.S. monetary policy played for asset markets of several emerging market economies in a period from January 2000 to October 2014. We employ multi-variate GARCH models in which we distinguish between a conventional and an unconventional monetary policy phase to account for possible heterogeneity in spillover effects. Our results suggest that the anticipation of loose U.S. monetary policy has diverse effects across monetary policy regimes. While spillovers have little impact on equity returns, they put pressure on local currencies. However, they increase conditional volatilities of both stock and exchange rate returns considerably in most emerging economies within the conventional monetary policy period. These effects can be stronger during unconventional monetary policy times. In accordance with these findings, we observe a tighter link between U.S. monetary policy and foreign asset markets during the unconventional monetary policy phase. Volatility impulse responses show that conditional volatilities of foreign asset markets mainly decrease in response to historical shocks. Particularly during unconventional monetary policy times, U.S. shocks gain importance in explaining the change in conditional volatilities especially for countries with less geographical distance to the United States.
Keywords: E43; E44; E52; 330; emerging markets; monetary policy spillovers; multivariate GARCH; unconventional monetary policy; quantitative easing